PENYULUHAN PENCEGAHAN 3 DOSA BESAR DALAM DUNIA PENDIDIKAN BAGI GURU DAN SISWA/I MAN 1 PULAU HARAPAN, KEP. SERIBU, JAKARTA - Badriyah; Andriani, Tri; Jajat Sudrajat; Ibar Adi Permana; Alfin Khaira (JURNAL ABDIMAS PLJ, 2024)
A safe, comfortable and disciplined school is a school where all school members are free from fear, intimidation, sexual violence and bullying so that a conducive atmosphere is created for learning and positive relationships between school members are established. Seeing the importance of understanding the consequences of the 3 major sins in Education, the LP3I Jakarta Polytechnic together with school members of SDN 01 and MAN 1, Pulau Harapan Village, Seribu Islands, conducted community service activities to create a healthy, child-friendly school culture environment. This training aims to increase knowledge and school members in Pulau Harapan, Seribu Islands, Jakarta regarding the 3 major sins of education. The method used is training and counseling attended by 25 teachers and students. The results of this community service are that it can increase knowledge and increase awareness of students in the 3 Great Sins in Education. The next activity that can be offered or suggested by the community service team is to provide soft skills training for students and self-development.